THU0330 Mycobacterial cord factor analog induces high il-6 secretion and mincle receptor expression in patients with takayasu arteritis. (15th June 2017) - Gupta, N; Doss, J Kabeer; Mohan, H; Goel, R; Danda, D
Abstract : Background: Association between Takayasu Arteritis (TA) and Tubcerculosis (TB) has been in vogue for years. Scientific evidence for this association is limited. Objectives: To study pro-inflammatory cytokine responses and mRNA expression in patients with TA on exposure to Trehalose-6, 6-dibehenate (TDB), a synthetic analogue of mycobacterial cord factor in comparison with healthy controls. Methods: Patients with type V TA satisfying 1990 ACR criteria and age and sex matched healthy controls were recruited. 10 ml blood was collected in heparin coated tube. PBMCs were separated by density gradient centrifugation. PBMCs were cultured with and without 5μg/ml and/or 50 μg/ml of TDB for 48 hours in RPMI medium at 5% co2 incubator. IL-6, TNF-αand IL-17 were measured in cell culture supernatant. RNA was extracted from the cells and quantification of gene expression was performed using sequence specific primers with SYBR green in Step One Plus™ Real-Time PCR Systems (Applied Biosystems). Results: Twenty two TA patients and 21 age and sex matched healthy controls were recruited. Baseline characteristic of cases included median (range) age:26.5 years (15–49), male:femaleratio of 5:17, ITAS-CRP2010: 7 (1–26) and DEITAK: 7.5 (1–21). Both patients and controls showed response by secreting IL-6 and TNF-α upon stimulation withTDB. Relative induction of IL-6 was significantly higher in TA [31.88 (0.74–168)] as compared to healthy controls [1.931 (0.644–8.21); p<0.002]. IL-17 was undetectable even upon TDB stimulation. Relative mincle expression was significantly upregulated by TDB in TA1.03 (0.623–1.346) fold, as compared to healthy controls 0.43 (0.36–0.57) fold (p<0.05). Relative gene expressions of IL-6, IL-8, TNFα, IFN-gand BCL-10 were not significantly different between TA and healthy controls. Conclusions: Stimulation with TDB led to higher secretion of IL-6 and increased mincle expression in PBMCs of TA patients as compared to healthy controls. Disclosure of Interest: None declared